Elastic local buckling strength analysis of stiffened aluminium plates with an emphasis on the initial deflections and welding residual stresses. (17th February 2019) - Mohammadi, Milad; Khedmati, Mohammad Reza; Bahmyari, Ehsan
ABSTRACT: This study aims at estimation of the elastic local buckling strength of stiffened aluminium plates. First, the patterns of initial deflections and welding residual stresses are studied in details. Then, the energy-method-based Fujikubo–Yao's algorithm is so modified that the assessment of the elastic local buckling strength of the stiffened aluminium plates becomes possible focusing on the specific characteristics of welding residual stresses and initial deflections. The modified algorithm is implemented into a computer code in MATLAB environment, where it is verified against the FEM. Three groups of the stiffened aluminium plates are considered and used for some further parametric studies.